Lipoblastoma in children: Review of 12 cases. Issue 5 (7th April 2017) - Susam‐Sen, Hilal; Yalcin, Bilgehan; Kutluk, Tezer; Cahit Tanyel, Feridun; Haliloglu, Mithat; Orhan, Diclehan; Aydin, Burca; Kurucu, Nilgun; Varan, Ali; Akyuz, Canan
Abstract: Background: Lipoblastoma is a rare benign mesenchymal tumor of infancy and early childhood. Symptoms vary depending on localization, and signs of compression of adjacent organs may be seen. Methods: A total of 12 children with pathologically proven lipoblastoma from 2000 to 2014 were reviewed retrospectively for their clinical features, treatment and follow up. Results: There were seven boys and five girls between 7.5 months and 7.5 years of age. The most common symptom was painless rapid‐growing mass. The tumors were located in the neck, the abdomen, the groin, pelvis, axilla, glutea, labium majus, thigh and trunk. The largest tumor was in a retroperitoneal location and was 13 × 10 cm in size. Complete resection was performed in 10 patients. All of these patients were followed without any evidence of recurrence. Subtotal excision was performed in two patients. At a median follow up of 38 months (range, 1.8 months–10 years), all patients were disease free. Conclusions: Lipoblastoma should be considered in the differential diagnosis of rapidly growing mass in patients <3 years of age. Total excision is the treatment of choice with preservation of vital organs. The prognosis is excellent despite large tumor size and local invasion. Recurrence rate is high in incompletely resected tumors. Regular follow up is important for early detection of recurrence.